A Polyoxometalate‐Based Binder‐Free Capacitive Deionization Electrode for Highly Efficient Sea Water Desalination. Issue 19 (12th March 2020) - Liu, Hang; Zhang, Juan; Xu, Xinxin; Wang, Qiang
Abstract: Capacitive deionization is a promising technique in sea water desalination. Compared with common electrodes, mixed capacitive‐deionization electrodes exhibit better performance in sea water desalination because they integrate pseudocapacitance and electric double‐layer capacitance in one system. Herein, a 3D binder‐free mixed capacitive‐deionization electrode was fabricated by direct electrodeposition of SiW12 O40 4− and polyaniline on a 3D exfoliated graphite carrier. In this electrode, SiW12 O40 4− /polyaniline composite particles with a size of about 100–120 nm are dispersed homogenously on the 3D exfoliated graphite carrier. Its specific capacitance reaches 352 F g −1 at 1 A g −1 . With increasing current from 1 to 20 A g −1, the specific capacitance only decays by 32 %. When employed in sea water desalination, the performance of this mixed capacitive‐deionization electrode is also excellent. At 1.2 V, the salt adsorption capacity of this mixed electrode reaches 23.1 mg g −1 with a salt adsorption rate of 1.38 mg g −1 min −1 in 500 mg L −1 NaCl. The performance of this electrode is well retained after 30 cycles. The excellent sea water desalination performance originates from the synergistic effect between SiW12 O40 4− and polyaniline. This work has developed polyoxometalate as a new material for capacitive‐deionization electrodes. Abstract : Mixed‐capacitive electrodes : Binder‐free deionization electrodes fabricated by electrodeposition of SiW12 O40 4− and polyaniline on a 3D exfoliated graphite carrier exhibiting a combination of pseudocapacitance and electric double‐layer capacitance show excellent performance in water desalination due to the synergistic effect between the polyoxometalate and the polymer.